2017
DOI: 10.1038/s41598-017-09879-7
|View full text |Cite
|
Sign up to set email alerts
|

Tribochemistry of adaptive integrated interfaces at boundary lubricated contacts

Abstract: Understanding how an adaptive integrated interface between lubricant additives and solid contacts works will enable improving the wear and friction of moving engine components. This work represents the comprehensive characterization of compositional and structural orientation at the sliding interface from the perspective of surface/interface tribochemistry. The integrated interface of a lubricant additive-solid resulting from the friction testing of Graphite-like carbon (GLC) and PVD-CrN coated rings sliding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Furthermore, the COF reduction efficiency ( ɳ EF ) of lubricating oil mixtures versus base oil was calculated by using the Equation and COF reduction efficiency of % 1, 3, and 5 ZDDP, and boric acid mixtures were 56%, 61%, and 64%, respectively. These results suggested that an increase in the concentration of boric acid and ZDDP slightly increased the COF reduction efficiency of steady state friction regimes at boundary lubrication regime ɳEF%=COFaverage0.25em()Base oilCOFaverage0.25em()ZDDP or Boric acidCOFaverage0.25em()Base oil×100. …”
Section: Resultsmentioning
confidence: 87%
“…Furthermore, the COF reduction efficiency ( ɳ EF ) of lubricating oil mixtures versus base oil was calculated by using the Equation and COF reduction efficiency of % 1, 3, and 5 ZDDP, and boric acid mixtures were 56%, 61%, and 64%, respectively. These results suggested that an increase in the concentration of boric acid and ZDDP slightly increased the COF reduction efficiency of steady state friction regimes at boundary lubrication regime ɳEF%=COFaverage0.25em()Base oilCOFaverage0.25em()ZDDP or Boric acidCOFaverage0.25em()Base oil×100. …”
Section: Resultsmentioning
confidence: 87%
“…Among them, TiSiN exhibits the highest hardness with up to a theoretical value of 105 GPa . However, the microcracks are often observed in ceramic coatings during service, and some of them are internal and make the coating uncompacted while the others can penetrate the whole coating and result in the exposure of the substrate. According to Farid and Bai, although Ti–6Al–4V with the TiSiN coating demonstrated a better performance in electrochemical impedance spectroscopy (EIS) experiments than the uncoated one, algae can still adhere to its surface due to the failure of the coating induced by microcracks.…”
Section: Introductionmentioning
confidence: 99%
“…The biolubricants displayed improved and acceptable wear and lubricity behaviour than the petroleum based‐lubricant, depending on their proposed applications. Other recent applications of biolubricants prepared by the esterification and transesterification process with enhanced tribological behaviours have been reported by Hamdan et al, 172 Hassan et al, 173 Wan et al, 174 Ameen et al, 175 Pérez‐de Brito et al, 176 and Gemsprim et al 177 However, biolubricants in the preceding years underperformed in certain applications at high temperatures and highly oxidative environments, affecting their tribological performance. This is because the maximum of the produced biolubricants is obtained from vegetable sources, with some portions containing high unsaturated fatty acids exposing them rapidly to lipid oxidation.…”
Section: Chemical Modification Of Oils For Biolubricants Synthesismentioning
confidence: 99%